2008
DOI: 10.1016/j.biopsych.2008.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neuroimmune Biomarkers in Sweat Patches and Plasma of Premenopausal Women with Major Depressive Disorder in Remission: The POWER Study

Abstract: Background-Major depressive disorder (MDD) is inconsistently associated with elevations in pro-inflammatory cytokines and neuropeptides. We used a skin sweat patch, recently validated in healthy controls, and recycling immunoaffinity chromatography (RIC), to measure neuroimmune biomarkers in patients with MDD mostly in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
163
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(181 citation statements)
references
References 19 publications
7
163
2
6
Order By: Relevance
“…In addition, we have shown that IL-6 does not appear in sweat in concentrations similar to, or even above that of plasma, counter to previous reports (Cizza et al 2008;Marques-Deak et al 2006). Therefore, in agreement with previous proteomic analysis of sweat (Raiszadeh et al 2012), it is unlikely that sweat acts as a plasma transudate, at least in the case of IL-6.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In addition, we have shown that IL-6 does not appear in sweat in concentrations similar to, or even above that of plasma, counter to previous reports (Cizza et al 2008;Marques-Deak et al 2006). Therefore, in agreement with previous proteomic analysis of sweat (Raiszadeh et al 2012), it is unlikely that sweat acts as a plasma transudate, at least in the case of IL-6.…”
Section: Discussioncontrasting
confidence: 99%
“…The assay was sensitive enough to detect IL-6 in human sweat and plasma at concentrations greater than 0.31 pg.ml -1 , which is well below the normal physiological plasma range of this cytokine. Therefore, it is somewhat surprising that we were unable to replicate the findings of others that IL-6 is present in sweat at concentrations above that of blood plasma (Cizza et al 2008;Marques-Deak et al 2006).This is especially so given that female participants were used for this part of the study, in order to directly replicate the subject group of the previous work and that plasma IL-6 was detected at all time points within the expected physiological range.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations